Semiotic Analysis of Jokowi's Political Meme "the King of Lip Service" and "YNTKTS" as Media for Criticism in the Digital Age - Shakilah Faliha; Kinkin Yuliaty Subarsa Putri (Persepsi: Communication Journal, 2022)
New media have not only made significant changes to people's communication patterns but have also built a new system called cyber-democracy. One of the phenomena that are now a place for cyber-democracy and we can find it in the density of content on the internet is memes. Memes, now referred to as internet memes, are considered promotional media that can reach a broader audience in a short time and are used by social media users as a new medium of communication to express humour with a satirical meaning. One is how memes are used to voice political aspirations and criticism or commonly known as political memes. One of the political memes that had gone viral was a political meme about President Joko Widodo on social media Twitter. Therefore, this study aims to analyze the semiotic elements in Joko Widodo's political meme circulating on social media Twitter using Charles Sanders Peirce's semiotic analysis and explain how the condition of Indonesian democracy with memes as media criticism in the digital era. The results of the study revealed that the meme did not disappoint the public towards President Joko Widodo and how democracy was limited by the Indonesian government which still did not fully accept political humour as a form of criticism.